2000
DOI: 10.1038/sj.pcan.4500424
|View full text |Cite
|
Sign up to set email alerts
|

Use of pretreatment prostate-specific antigen doubling time to predict outcome after radical prostatectomy

Abstract: The objective of this study was to better understand the implications of the rate of prostate-speci®c antigen (PSA) changes in prostate carcinoma. We retrospectively calculated PSA doubling times prior to surgery in 62 patients with prostate carcinoma. The calculated values were compared with ®nal pathologic ®ndings and with rates of PSA failure after surgery. PSA values increased during the period of observation in 82.3% of the patients, whereas 17.7% had levels that remained stable. The median calculated PSA… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
25
0
2

Year Published

2006
2006
2016
2016

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 45 publications
(29 citation statements)
references
References 10 publications
2
25
0
2
Order By: Relevance
“…The finding that tumor growth rate is of critical importance in determining outcome is consistent with other studies that have examined tumor doubling times, albeit in the absence of therapy 3437. It is important to note that there is a fixed ratio between any determined growth rate constant and the doubling time, a fact well known to enzyme kineticists.…”
Section: Discussionsupporting
confidence: 84%
“…The finding that tumor growth rate is of critical importance in determining outcome is consistent with other studies that have examined tumor doubling times, albeit in the absence of therapy 3437. It is important to note that there is a fixed ratio between any determined growth rate constant and the doubling time, a fact well known to enzyme kineticists.…”
Section: Discussionsupporting
confidence: 84%
“…The results in the present study are similar to those mentioned by Egawa et al (20). In addition, in the present paper, it has been demonstrated that pre-PSADT is an independent factor for PSA failure, similar to the results obtained for the biopsy Gleason score and clinical stage via the multivariate logistic regression analysis (Table IV).…”
Section: P-value (Hr 95% Ci) a -------------------------------------supporting
confidence: 81%
“…However, in their study, the median followup period following radical surgery was only 17.3 months, which they reported was an improvement compared with conducting a longer follow-up to examine the correlation of pre-PSADT with the pathological stage and PSA failure. Egawa et al (20) retrospectively studied pre-PSADT in 62 patients with T1-3N0M0 prostate cancer, and reported that pre-PSADT is significantly associated with the final pathological stage and PSA failure following radical prostatectomy. Pathological stage, n (%) Specimen Gleason score, n (%) Early PSA failure was revealed to be more common in patients with rapid PSADT.…”
Section: Discussionmentioning
confidence: 99%
“…Another limitation is the absence of PSA history for this cohort of very low risk prostate cancer that underwent surgery. It is common to advise against active surveillance in men with a PSA doubling time (PSADT) < 3 years 2930 or if there is a rise in PSA of more than 2 ng/ml/y before starting active surveillance 3132 . It cannot be entirely ruled out that the lack of data on PSA history, as well as the absence of a repeat biopsy, may influence the extent of adverse pathology after surgery in this study.…”
Section: Discussionmentioning
confidence: 99%